A brain penetrant progranulin biotherapeutic rescues lysosomal and inflammatory phenotypes in the brain of GRN knockout mice: Lipids in AD and FTD: From genes to interventions. (7th December 2020) - Logan, Todd; DeVos, Sarah; Simon, Matthew J.; Davis, Sonnet; Wang, Junhua; Low, Ray; Huang, Fen; Rajendra, Yashas; Prorok, Rachel; Sun, Elizabeth; Rana, Anil; Hsiao‐Nakamoto, Jennifer; et al.
Abstract: Background: Heterozygous loss of function (LOF) mutations in GRN cause frontotemporal dementia (FTD), a neurodegenerative disorder associated with lysosomal dysfunction, TDP‐43 pathology and inflammation in the CNS. Additionally, homozygous LOF mutations cause neuronal ceroid lipofuscinosis, a lysosomal storage disorder. GRN encodes progranulin (PGRN), a soluble protein that is most abundantly expressed in microglia, where it localizes to lysosomes and can undergo secretion. Although the precise function of PGRN is unknown, growing evidence suggests that it regulates lysosomal function, inflammatory responses and promotes neuronal survival. Accordingly, PGRN LOF models are associated with lysosomal defects, hyperinflammatory responses, and decreased neuronal viability, both in vitro and in vivo . Because GRN ‐FTD patients exhibit reduced levels of PGRN in biofluids and tissues, including the brain, a protein replacement therapy analogous to enzyme replacement therapy and capable of crossing the blood brain barrier (BBB) more efficiently may represent a powerful approach to slow or prevent disease progression. Method: Here we describe a novel therapeutic for increasing brain penetrance of PGRN, referred to as Protein Transport Vehicle (PTV):PGRN. PTV:PGRN consists of recombinant human PGRN fused to a modified Fc domain engineered to bind to the human transferrin receptor (huTfR), thus facilitating receptor‐mediated transcytosis across the BBB. Result: We found that extracellular applications of PTV:PGRN rescue a range of Grn KO cell phenotypes in vitro, including lysosomal proteolysis and alteration in the levels of bis(monoacylglycero)phosphate (BMP), an endolysosomal phospholipid involved in lysosomal lipid catabolism. Intravenously administered PTV:PGRN showed increased acute brain exposure in huTfR knock‐in (TfR mu/hu ) mice relative to a regular Fc:PGRN fusion that does not bind to huTfR. Importantly, low doses of PTV:PGRN, but not Fc:PGRN, fully corrected lysosomal lipid alterations, including BMP deficiency, as well as inflammatory markers in the brain of Grn KO x TfR mu/hu mice. Conclusion: Our data suggest that PTV:PGRN may represent a viable therapeutic strategy for the treatment of GRN ‐FTD and potentially other disorders associated with PGRN deficiency.